Distribution and metabolism in healthy volunteers of disodium azodisalicylate, a potential therapeutic agent for ulcerative colitis. Issue 12 (December 1982) - Willoughby, C P; Aronson, J K; Agback, H; Bodin, N O; Truelove, S C
Abstract : A series of experiments has been performed in healthy male volunteers to investigate the disposition of orally administered disodium azodisalicylate, a potentially useful drug for the treatment of ulcerative colitis. The drug was given by mouth in doses of up to 2 g a day for six weeks and there were no adverse effects. Serum concentrations of the intact compound were low and the serum half-time was 4-12.8 days, probably because of a combination of a low clearance rate and a high apparent volume of distribution. Less than 5% of the ingested dose was excreted unchanged in the urine. Circulating concentrations of 5-ASA and N-acetyl-5-ASA were low and 30% of the equivalent daily dose was excreted in the urine, predominantly as N-acetyl-5-ASA. In most subjects more than 30% of the equivalent daily dose of 5-ASA was recovered from the faeces, either as 5-ASA itself or as the acetylated derivative. As 5-ASA has been shown to be the active therapeutic moiety of sulphasalazine, disodium azodisalicylate appears to be suitable for therapeutic trial in ulcerative colitis.